1988
DOI: 10.1159/000461828
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Microsphere Method for the Investigation of Erythrocyte Chimaerism after Allogeneic Bone Marrow Transplantation Using Antigenic Differences

Abstract: A method for the investigation of erythrocyte chimaerism in patients after bone marrow transplantation (BMT) has been developed using fluorescent microspheres coated with anti-human IgG. Blood group antigens different in patient and donor were used as marker. The specificity and reliability of this method was evaluated measuring artificial mixtures of blood group positive and negative red cells. Red cell antigens tested were D, c, K, Fy^a, Fy^b, Jk^a, Jk^b, S and s. Mean linear regression lines for mixtures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Red blood cell phenotyping was performed using a flow cytometric and/or fluorescent microscopic microsphere method as described previously. [27][28][29] The sensitivity level is 0.1-0.3% for the flow cytometric method and 0.01% for the fluorescent microscopic technique. At the level of 0% patient or donor red cells, the flow cytometric results were always controlled by the fluorescent microscopic method in order to increase the sensitivity to a level of 0.01%.…”
Section: Chimerism Analyzed By Cytogenetic Analysis and Red Blood Celmentioning
confidence: 99%
“…Red blood cell phenotyping was performed using a flow cytometric and/or fluorescent microscopic microsphere method as described previously. [27][28][29] The sensitivity level is 0.1-0.3% for the flow cytometric method and 0.01% for the fluorescent microscopic technique. At the level of 0% patient or donor red cells, the flow cytometric results were always controlled by the fluorescent microscopic method in order to increase the sensitivity to a level of 0.01%.…”
Section: Chimerism Analyzed By Cytogenetic Analysis and Red Blood Celmentioning
confidence: 99%
“…Red blood cell phenotyping was performed using a flow cytometric and/or fluorescent microscopic microsphere method as described previously. [37][38][39] The sensitivity level is 0.1-0.3% for the flow cytometric method and 0.01% for the fluorescent microscopic technique. At the level of 0% patient or donor red cells, the flow cytometric results were always controlled by the fluorescent microscopic method in order to increase the sensitivity of this test to a level of 0.01% in this analysis.…”
Section: Assessment Of Gvhd Relapse and Chimerismmentioning
confidence: 99%
“…In a study carried out by using antibody-coated fluorescent microspheres, donor-derived EA was seen in 86% of the patients on the 15th day. 3 In another study, donor-derived antigens were observed at the end of 8th week in 71% of patients. 1 It is concluded that the tube agglutination technique is as efficient as antibody-coated fluorescent microspheres or gel tests in order to detect EA engraftment.…”
Section: Discussionmentioning
confidence: 93%
“…Later, anti-human IgG-coated fluorescence microspheres were used to detect chimerism. 3 Subsequently, gel test was used to differentiate donor and recipient RBCs. 4 Flow cytometric analysis using monoclonal antibodies directed against blood group antigens enabled sensitive evaluation of dual RBC populations.…”
mentioning
confidence: 99%